"I Wish the Hitting Would Stop . . . " An Assessment of a Domestic Violence Education Program for Elementary Students. (September 2014) - Dahle, Thorvald O.; Archbold, Carol A.
School officials across the country have recognized that many of their students live in homes where domestic violence occurs. As a result, several elementary schools have implemented education-based programs focused on this issue. The current study evaluates the efficacy of the "I Wish the Hitting Would Stop . . . " program that was presented to elementary school children in two school districts in the Midwest. This study examines the level of knowledge retention by students who participated in the "I Wish the Hitting Would Stop . . . " program during the 2010-2011 and 2011-2012 academic years. Fourth- and fifth-grade students responded to open-ended questions regarding their understanding of domestic violence and their retention of the concepts presented in the "I Wish the Hitting Would Stop . . . " curriculum. While the results suggest that students retain the information presented in the program, there also appears to be a gender difference in knowledge retention.